1985
DOI: 10.2134/agronj1985.00021962007700060003x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Root Temperature and Nitrate/Ammonium Ratio on Strawberry Plants. II. Nitrogen Uptake, Mineral Ions, and Carboxylate Concentrations1

Abstract: Strawberry plants (Fragaria ananasa Duch.) have shallow roots and are grown in the field during both hot and cold seasons. The possibility of irrigating and fertilizing the plants daily, through the trickle system, led to the question of what is the best nitrogen form and N03 /NHt ratios to be supplied to this crop during the growing season. The effect of four root temperatures (10, 17, 25 and 32 oq and five N03 /NHt mole ratios (0/7, 2/5, 3.5/3.5, 5/2, 7 /0) at constant total N in the solution was studied. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…However, in other studies with tomato, strawberry, or chrysanthemum, Mg uptake did not change as root-zone temperature changed (Ganmore-Neumann and Kafkafi, 1985;Kafkafi, 1990;Selmer-Olsen and Gislerod, 1982).…”
Section: Temperature Effect On Uptakementioning
confidence: 76%
See 1 more Smart Citation
“…However, in other studies with tomato, strawberry, or chrysanthemum, Mg uptake did not change as root-zone temperature changed (Ganmore-Neumann and Kafkafi, 1985;Kafkafi, 1990;Selmer-Olsen and Gislerod, 1982).…”
Section: Temperature Effect On Uptakementioning
confidence: 76%
“…A study with white clover showed no changes in NO3--N: NH4+-N uptake ratio as temperatures ranged from 3 to 25"C (Hatch and Macduff, 1991), while in a study with barley, the NO3--N.-NH4+-N uptake ratio varied greatly across root-zone temperatures (Macduff and Hopper, 1986). As root-zone temperatures increased, the NO3--N:NH4+-N uptake ratio either decreased or increased for strawberry and tomato, respectively (Ganmore-Newman and Kafkafi, 1985;Tindall et al, 1990).…”
Section: Temperature Effect On Uptakementioning
confidence: 99%
“…However, in early experiments conducted at constant N concentrations the solution temperature was not controlled (Clark, 1936;Kirkby and Mengel, 1967;Kafkafi et al, 1971). In a series of studies (Ganmore-Neumann and Kafkafi, 1980aKafkafi, , 1980bKafkafi, , 1983Kafkafi, , 1985, the N0 3 -INH/ ratios, root temperatures, total N and other nutrients, and pH of the nutrient solution were all kept constant by allowing the nutrient solution to flush the container at a rate of I Uh.…”
Section: Effect Of N-form and Root Temperaturesmentioning
confidence: 99%
“…A reduction in sugar concentration was found in N0 3 --and NH/ -fed plant roots at 25 °C, as compared to roots maintained at lO °C. Increasing the NH/ fraction in the nutrient solution caused Downloaded by [New York University] increasing damage to the root system with increasing root temperature, culminating in root death at 32 °C with only NH 4 +in the solution (Ganmore-Neumann and Kafkafi, 1983Kafkafi, , 1985.…”
Section: Effect Of N-form and Root Temperaturesmentioning
confidence: 99%
“…Nitrogen (N) is the major macronutrient required for optimum development and function of plants (Daliparthy et al, 1994;Marschner, 1995). Nitrogen nutrition and fertigation regime influence a range of processes that might affect flower quality, such as osmoregulation (Smirnof and Stewart, 1985;Salsac et al, 1987;Garcia et al, 1996), tissue water content (Gerendás et al, 1997), leaf water potential (Adler et al, 1996), sugars and organic acid contents (Ganmore-Newmann and Kafkafi, 1985;Chaillou et al, 1991), and uptake of other ions (Bar et al, 1997). Nitrogen affects plant growth and development (Gerendás et al, 1997;Walch-Liu et al, 2000;Gifford et al, 2008); gene expression and metabolism (Scheible et al, 2004;Vidal and Gutierrez, 2008) and a range of processes including photosynthesis (Shelp and Taylor, 1990), root respiration (Matsumoto and Tamura, 1981), water relations and uptake (Ragab, 1980;Guo et al, 2002), and secondary metabolism (Wang and Below, 1996).…”
Section: Introductionmentioning
confidence: 99%